Cessation of embolic signals after antithrombotic prevention is related to reduced risk of recurrent arterioembolic transient ischaemic attack and stroke. Issue 3 (1st March 2002) - Goertler, M; Blaser, T; Krueger, S; Hofmann, K; Baeumer, M; Wallesch, C-W
Abstract : Objectives: To evaluate the reduction of embolic signals after the initiation of an antithrombotic secondary prevention in patients with recent arterioembolic stroke and to determine the predictive value of decreased microembolism on the risk of early stroke recurrence. Methods: Eighty six consecutive patients (55 men, 31 women; mean age 60.6 years) with a non-disabling arterioembolic ischaemic event in the anterior circulation within the last 30 days and a medium grade or high grade stenosis (≥50%) of the ipsilateral carotid or middle cerebral artery underwent 1 hour transcranial Doppler monitoring as part of the admission examinations. Antithrombotic secondary prevention was started after completion of admission. Patients in whom embolic signals were detected underwent a second monitoring within 4 days (mean time 1.8 days). All patients were followed up prospectively to evaluate the relation between presence and persistence of embolic signals and the risk of recurrent transient ischaemic attack (TIA) and stroke within the next 6 weeks. Results: In 44 patients, embolic signals were detected at admission, a mean 5.4 days (range 0 to 21 days) after the initial event. Twenty five were positive for embolic signals also at the second monitoring, in 19 signals had ceased. Forty two patients without embolic signals at admission served as controls. During follow up, six ischaemic events (two stroke, three TIA, one amaurosis fugax) occurred in 25 patients with persisting embolic signals but none in 19 patients in whom signals had ceased by the second monitoring. One patient in the control group had a TIA. The incidence of a recurrent event was 0.45 per 30 patient-days if embolic signals persisted compared with 0.015 if signals could not be detected or had ceased. Persistence of embolic signals was an independent predictor of a recurrent TIA or stroke (adjusted odds ratio 37.0; 95% confidence interval (95% CI) 3.5 to 333; p<0.003). Cessation and decrease of embolic signals was associated with the administration of antiplatelet agents but not with anticoagulation with intravenous heparin (p<0.001). Conclusions: Rapid cessation of embolic signals detected in patients with recently symptomatic arterial stenosis decreases increased risk of an early ischaemic recurrence. Effect of antithrombotic agents on embolic signals might serve as a marker for their efficacy on preventing stroke recurrence.